Copyright violation of predators in scientific publishing - Biochemia Medica's harmful experience and proposed solution - Pašalić, Daria (Array, 2020)
Biochemia Medica is an open access journal that does not charge manuscript processing or publishing. All editorial staff are continuously educated and directed to follow the highest ethical and scholarly publishing standards in all steps of the manuscript processing. They are all laboratory medicine professionals, who apart from their regular jobs, are in charge of different phases in Journal processing as volunteers. The publisher of the Journal is scientific and professional association of laboratory medicine professionals, Croatian Society of Medical Biochemistry and Laboratory medicine (CSMBLM).During November and December 2018, without knowledge of the editorial staff, unknown perpetrator(s) downloaded a respectable number of articles published in Biochemia Medica as PDF and launched an illegal web page under the same journal name with downloaded articles. Although this was a very harmful experience, we have learned a lot from it and we would like to share this with scientific journals’ community. Therefore, we would like to share this harmful experience, and to present a short workflow on how to manage situations like this if it will be necessary for any scientific journal in the future.